2020
DOI: 10.21608/ebwhj.2019.17496.1026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Thyroid Function in Pregnant Females Attending Suez Canal University Hospital

Abstract: Background: Pregnancy is a physiological state in which significant changes in thyroid function occur. Several factors contribute to these changes. These factors could contribute to thyroid dysfunction during pregnancy especially when a deficiency of iodine intake exists and when thyroid reserve is not sufficient. Aim: To study thyroid functions in pregnant women avoiding maternal and fetal complications associated with thyroid dysfunctions. Materials and Methods: A cross-sectional study was carried out on 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Against our findings was Abo El-Roose et al (12) who reported in their study on 100 pregnant women that most of the pregnant women had normal thyroid functions (51%) and 49% of the studied population had thyroid disorder. They also reported that subclinical hypothyroidism was the most prevalent disorder representing 39% of the total population followed by 6% had clinical hypothyroidism and 4% had isolated hypothyroxiemia.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Against our findings was Abo El-Roose et al (12) who reported in their study on 100 pregnant women that most of the pregnant women had normal thyroid functions (51%) and 49% of the studied population had thyroid disorder. They also reported that subclinical hypothyroidism was the most prevalent disorder representing 39% of the total population followed by 6% had clinical hypothyroidism and 4% had isolated hypothyroxiemia.…”
Section: Discussionsupporting
confidence: 41%
“…In agreement with our findings regarding patients' ages was Dulek et al (10) who reported that there was no statistical significant difference between different groups regarding their ages, gravidity and parity. Also, Abo El-Roose et al (12) found that no statistical significant difference between different thyroid functions and age was revealed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation